Kesalahan-kesalahan Dalam Percetakan Mushaf Al-quran Di Malaysia - Khairul Anuar Mohamad; Mohd Hasbie al-Shiddieque Ahmad (Usuli Faqih Research Centre PLT., 2024)
In Malaysia, the use of Al-Quran of Uthamani’s script has been empowered through the approach and exposure initaitives by Ministry of Home Affair’s. However, there are certain irresponsible al-Quran printing companies which ignored and abused the act of Printing of Quranic Text Act 1986. This study aims to identify errors in printing manuscripts of the Quran in Malaysia. It uses qualitative methods through interviews and data analysis instrument. The study found that there are some Quran printing errors such as no approval from the ministry, translation of Al-Quran without Arabic text, Quran writing not in accordance with rule of Uthamani’s script and translation errors in the text of the Quran are in contravention of the Printing of Quranic Text Act 1986.